Filtering with Limited Information - Thorsten Drautzburg; Jesús Fernández-Villaverde; Pablo Guerrón-Quintana; Dick Oosthuizen (CESifo GmbH, 2024)
We propose a new tool to filter non-linear dynamic models that does not require the researcher to specify the model fully and can be implemented without solving the model. If two conditions are satisfied, we can use a flexible statistical model and a known measurement equation to back out the hidden states of the dynamic model. The first condition is that the state is sufficiently volatile or persistent to be recoverable. The second condition requires the possibly non-linear measurement to be sufficiently smooth and to map uniquely to the state absent measurement error. We illustrate the method through various simulation studies and an empirical application to a sudden stops model applied to Mexican data.
Keywords: C32; C53; E37; E44; O11; 330; filtering; limited information; non-linear model; dynamic equilibrium model; sudden stops